2022
DOI: 10.1063/5.0085967
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant effects on microfluidic extensional flow of water and polymer solutions

Abstract: Surfactants are often added to particle suspensions in the flow of Newtonian or non-Newtonian fluids for the purpose of reducing particle-particle aggregation and particle-wall adhesion. However, the impact on the flow behavior of such surfactant additions is often overlooked. We experimentally investigate the effect of the addition of a frequently used neutral surfactant, Tween 20, at the concentration pertaining to microfluidic applications on the entry flow of water and three common polymer solutions throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
4
1
Order By: Relevance
“…We note that Dacus et al. (2022) observed that Tween-20 can affect the rheology of XG solutions in water; however, we observe a negligible effect on the rheology of our glycerol–water solvents, likely due to their high glycerol concentration (cf. solutions 2–5 in table 1).…”
Section: Methodscontrasting
confidence: 54%
See 1 more Smart Citation
“…We note that Dacus et al. (2022) observed that Tween-20 can affect the rheology of XG solutions in water; however, we observe a negligible effect on the rheology of our glycerol–water solvents, likely due to their high glycerol concentration (cf. solutions 2–5 in table 1).…”
Section: Methodscontrasting
confidence: 54%
“…The solution was covered and placed on a magnetic stirrer for 24 h. Tween-20 (T20) surfactant (Sigma-Aldrich; CAS: 9005-64-5) was then added to the solution in concentrations 0.02-4 %w. We note that Dacus et al (2022) observed that Tween-20 can affect the rheology of XG solutions in water; however, we observe a negligible effect on the rheology of our glycerol-water solvents, likely due to their high Label Glycerol/water (%) φ (ppm) T20 (%) NaCl (%) σ (mN m −1 ) β (mPa s n ) n glycerol concentration (cf. solutions 2-5 in table 1).…”
Section: Rheology Of Xg Solutionsmentioning
confidence: 99%
“…The vortices in the XG solution are only slightly smaller than those in water, consistent with our recent observations. 26,34 In contrast, the vortices in the PEO solution are significantly smaller, which may again indicate the stronger impact of fluid elasticity than shear thinning on the expansion flow. It is, however, unclear to the authors why the vortices in the PAA solution, which is more shear thinning than the XG solution and more viscoelastic than the PEO solution, are not the smallest among the tested fluids.…”
Section: Resultsmentioning
confidence: 99%
“…on the contraction and/or expansion polymer flow. [18][19][20][21][22][23][24][25][26] In addition, many other papers have studied the effects of fluid rheological properties such as shear thinning/thickening and viscoelasticity. [28][29][30][31][32][33][34][35][36] The length and width of the contraction and/or expansion microchannels in previous studies are usually kept much larger than the depth constructing a pseudo-Hele-Shaw configuration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation